Research status of clinical application of moxibustion (艾灸疗法临床应用研究现状) - LIU Yanna (刘燕娜); FAN Yan (范艳); WANG Xuesong (王雪送); YANG Yu (杨宇); HU Shirong (胡世荣) (Association of Integrative Nursing, 2021)
Moxibustion therapy is now widely used in the treatment and prevention of diseases in the clinical settings. This paper summarized the research status of moxibustion therapy in the treatment of hypertension, insomnia, anxiety, depression and pain, in order to promote its application in clinical settings and provide reference for the innovative development. (艾灸疗法在临床被广泛应用于治疗和预防疾病。本文总结归纳艾灸疗法在高血压、失眠、焦虑抑郁情绪以及疼痛中的应用现状, 以期为在临床工作中推广艾灸疗法, 为艾灸疗法创新性发展提供参考。)